PELAKSANA SURAT KETERANGAN WARIS OLEH PEJABAT NOTARIS DI 5 KOTA JAKARTA, BANDUNG , SEMARANG, YOGYAKARTA , SURAKARTA - Lidwina Maria T.; A.Aris Swantoro; Putri Purbasari Raharningtyas Marditia (Universitas Katolik Indonesia Atma Jaya, 2019)
Notary is an official appointed by the Government based on the Notary Position Regulation to be able to make a deed. The Notary is required to be responsible for the contents of the deed made by the parties so that it does not contradict the Regulation of the Notary Position, and or does not make a deed that does not meet the requirements in advance of shipping or contrary to the provisions of Article KUHPEr. So that the Notary in carrying out his responsibilities must not conflict with the authority specified in the regulations. One deed that can be made by a Notary Public is a certificate of inheritance SKW. In practice the making of SKW is not as small as a Notary who was fooled in bad faith from the parties in terms of the contender giving a fake Birth Certificate so that the Notary Public means that those who are facing are the heirs who should and are entitled to and get an inheritance. But related to this matter, if in the future the SKW is problematic it will not be the responsibility of the Notary. Civil liability can occur in 2 cases Acts against the Law and Default. Violation of Unlawful Acts by a Notary is to act beyond or contradict the responsibility that has been given to him as stipulated in the regulations relating to the making of the deed. The practice that becomes the responsibility of a notary in making SKW is as follows: First, Error in applying the article related to the distribution of inheritance. Second, mistakes in determining the parties who become heirs in good faith. Third, the error determines the amount of distribution for each heir determined by SKW. Fourth, the testator's will is not included in the SKW made by the parties. Notary in practice can avoid this risk if among the Notary professions determine and determine the procedures and prerequisites for making and format of SKW as the notary profession agrees to the code of ethics so that uniformity of the Notaries in making SKW thus prevents the Notary from legal liability that should be can be avoided in carrying out his responsibilities as a Notary